Delayed Presentation of Vaginal Cuff Dehiscence after Robotic Hysterectomy for Gynecologic Cancer: A Case Series and Review of the Literature. (27th March 2016) - Escobar, Pamela A.; Gressel, Gregory M.; Goldberg, Gary L.; Kuo, Dennis Yi-Shin
Abstract : Background . Vaginal cuff dehiscence after hysterectomy has varying incidence according to surgical approach, with highest rates associated with laparoscopic surgery. Comparative data on timing of diagnosis describe a wide range of clinical presentation from weeks to years after hysterectomy. Limited reports have focused specifically on delayed presentation of vaginal cuff dehiscence. Cases . All cases of vaginal cuff dehiscence at our institution between 2005 and 2015 were collectively reviewed and three cases were identified of women who presented with cuff dehiscence greater than 180 days from index surgery. Diagnosis occurred at 342 to 461 days after operation. One patient presented with abdominal pain, a second case presented with vaginal discharge, and the third case lacked clinical symptoms altogether. Prior to diagnosis, one case received chemotherapy and external beam radiation for Stage IB1 cervical cancer and another case received external beam radiation alone for Stage II endometrioid adenocarcinoma. All cuffs were repaired vaginally with interrupted, early absorbable suture. Conclusion . Robotic total laparoscopic hysterectomy may be associated with increased risk of vaginal cuff dehiscence. Further studies are needed to determine risk factors and patient characteristics associated with delayed presentation of vaginal cuff dehiscence in robotic total hysterectomy as well as all surgical approaches.